2016
DOI: 10.1038/s41598-016-0001-8
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Characterization of the Lower Motor System in a Mouse Model of Krabbe Disease

Abstract: Krabbe disease (KD) is a neurodegenerative disorder caused by the lack of β- galactosylceramidase enzymatic activity and by widespread accumulation of the cytotoxic galactosyl-sphingosine in neuronal, myelinating and endothelial cells. Despite the wide use of Twitcher mice as experimental model for KD, the ultrastructure of this model is partial and mainly addressing peripheral nerves. More details are requested to elucidate the basis of the motor defects, which are the first to appear during KD onset. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

331
6,515
34
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15,627 publications
(6,889 citation statements)
references
References 43 publications
331
6,515
34
9
Order By: Relevance
“…(Left) A photograph of the tubule structure being fabricated on the 3D printer with a collagen gel; (Left middle) A 3D confocal microscopic reconstruction of the engineered tubule structure lined by fluorescently labeled human proximal tubular epithelial cells; (Middle right) A high magnification fluorescence microscopic image of the engineered tubule showing that it is lined by a continuous layer of fluorescent epithelial cells; and (Right) A higher magnification fluorescence microscopic cross‐sectional view through the engineered tubule demonstrating that it is lined by a continuous polarized kidney proximal tubular epithelium (e.g., expressing Na+/K+ ATPase only on its basolateral surface). [Work of Jennifer Lewis and the 3D Organ Engineering Initiative]21 …”
Section: The Institute's Platform Focus Areas and Initiativesmentioning
confidence: 99%
“…(Left) A photograph of the tubule structure being fabricated on the 3D printer with a collagen gel; (Left middle) A 3D confocal microscopic reconstruction of the engineered tubule structure lined by fluorescently labeled human proximal tubular epithelial cells; (Middle right) A high magnification fluorescence microscopic image of the engineered tubule showing that it is lined by a continuous layer of fluorescent epithelial cells; and (Right) A higher magnification fluorescence microscopic cross‐sectional view through the engineered tubule demonstrating that it is lined by a continuous polarized kidney proximal tubular epithelium (e.g., expressing Na+/K+ ATPase only on its basolateral surface). [Work of Jennifer Lewis and the 3D Organ Engineering Initiative]21 …”
Section: The Institute's Platform Focus Areas and Initiativesmentioning
confidence: 99%
“…Third, disrupted sleep increases sympathetic nervous activity, leading to an increase in blood pressure and heart rate, which demands cardiac activity at a time when the heart should be regenerating 2, 19, 20. In addition, several studies have shown that SA is associated with hypertension, coronary artery disease, arrhythmias, obesity, diabetes mellitus, and metabolic disturbances, all known to increase the risk of HF 2, 3, 21, 22. Hence, we applied many of these comorbidities in our regression models, including continuous assessment of their presence.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep apnea (SA) is associated with increased risk of cardiovascular events, worsening of heart failure (HF), metabolic disturbances, and overall a reduced quality of life 1, 2, 3, 4. One study even found an increased risk of incident HF among men with obstructive sleep apnea (OSA) 5.…”
mentioning
confidence: 99%
“…Recently, dye‐modified UCNPs can also be used as pH probes for the application in living cells. For example, different energy acceptors such as xylenol orange90 and fluorescein isothiocyanate91, 92 have been reported.…”
Section: Ucnp‐based Nanoprobes For Different Analyte Detectionmentioning
confidence: 99%
“…Song and co‐workers employed platinum complexes as energy acceptors to construct O 2 probe. The outside of this probe is coated with an ultrathin layer silane,97 which affords a hydrophobic environment to hold hydrophobic molecules for the realization of multifunctions.…”
Section: Ucnp‐based Nanoprobes For Different Analyte Detectionmentioning
confidence: 99%